PHYSICAL THERAPY OF CEPHALGIA IN DYSPLASTIC INSTABILITY OF THE CERVICAL SPINE IN CHILDREN - Gorsha, O.V.; Korolenko, N.V.; Shkolna, M.V.; Strashko, Y.Yu. (World of Medicine and Biology, 2020)
The purpose of the study was to investigate the effects of Kinesio Taping and therapeutic exercises on the clinical condition and hemodynamics of the vessels of the vertebrobasilar basin in children of primary school age with headache syndrome on the background of instability of the cervical spine. The study showed that the comprehensive use of these children in these methods of physical therapy has reduced the manifestation of pain (reduction of the frequency and intensity of headache), optimize the hemodynamics (blood flow, elastic properties of blood vessels, response to negative extravasal effects of the surrounding structures, venous outflow). The studied methods do not allow for a long time (6 months) to keep all the achieved clinical and functional results at the same level, although mostly they remain better than before treatment (p